A study on user awareness towards 3G services in Klang Valley / Norhafidzah Abd Ghafur - Abd Ghafur, Norhafidzah (Faculty of Computer and Mathematical Sciences, 2005)
Malaysia is now in pre-commercial stage of the third generation (3G) of mobile communications technology. 3G is a new universal system which could operate anywhere, anytime using unified equipment and offer bandwidth up to 2 Kbps. The objectives of this research paper are to identify the 3G services provided for Malaysians and to investigate awareness of people in Klang Valley towards 3G services. Interview and survey are two methods of data collections that have been used in this research. Two telecommunications companies have been interviewed (Maxis Communications (M) Sdn Bhd and Telekom Malaysia Bhd) in order to meet the first objective. 212 respondents (people in Klang Valley) have been selected to answer a set of questionnaires. Data collected were analyzed by using SPSS and Microsoft Excel. Results showed that the awareness level of people in Klang Valley towards 3G services is low. Therefore, telecommunications companies in Malaysia are suggested to think or create strategies on how to increase the awareness level of people in Klang Valley towards 3G services.